Balanced scorecards & operational dashboards with Microsoft Excel - Person, Ron. ([Indianapolis, IN?] : Wiley, 2013)
Learn to maintain and update scorecards and dashboards with Excel Balanced Scorecards and operational dashboards measure organizational performance and Microsoft Excel is the tool used worldwide to create these scorecards and dashboards. This book covers time-proven step-by-step processes on how to guide executive teams and managers in creating scorecards and dashboards. It then shows Excel developers how to create those scorecards and dashboards. This is the only book that converts theory into practice. The author addresses the people and processes you need to identify strategy ...
pt. 1. Strategic performance with balanced scorecards -- pt. 2. Operational performance with dashboards -- pt. 3. Building maps, scorecards, and dashboards.
Online resource; title from cover page (viewed September 3, 2013).
Keywords: Microsoft Excel (Computer file); Microsoft Excel (Computer file); Microsoft Excel (Computer file); Performance technology; Dashboards (Management information systems); COMPUTERS -- Management Information Systems; Dashboards (Management information systems); Performance technology; Electronic books; Electronic books